ORIGINAL ARTICLEpyoderma gangrenosum: a clinical analysis of 22 cases treated in Department of Dermatology, Medical University of Wroclaw in years 2000-2004 - Jankowska-Konsur, Alina; Maj, Joanna; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2006)
Abstract Pyoderma gangrenosum (PG) is an uncommon, idiopathic cutaneous disease, which rapidly progresses from painful pustules or vesicles into ulcers with well defined, violaceous, undermined borders. The lesions usually affect lower extremities but they may occur in any location. It is frequently associated with a wide spectrum of systemic diseases like inflammatory bowel disease (ulcerative colitis, Lesniowski-Crohn’s disease), arthritis, haematological, immunological and hepatic disorders. The diagnosis is established based on distinctive clinical features and exclusion of other causes of ulceration. The management of PG includes both topical and systemic therapy. Herein, we present 22 patients with PG treated at our department in years 2000-2004. The male to female ratio was 1:1. The average age of the onset of the disease was 52.7 years. Lower extremities, particularly shanks were affected most commonly (54.5%). In 10 patients the skin lesions were present in more than 1 body region. Systemic diseases were found in 13 patients. Of them, inflammatory bowel disease and haematological disorders were the most common.